Passive Heating Attenuates Post-exercise Cardiac Autonomic Recovery in Healthy Young Males - Peçanha, Tiago; Forjaz, Cláudia L. de Moraes; Low, David A. (Frontiers in Neuroscience, 2017)
Post-exercise heart rate (HR) recovery (HRR) presents a biphasic pattern, which is mediated by parasympathetic reactivation and sympathetic withdrawal. Several mechanisms regulate these post-exercise autonomic responses and thermoregulation has been proposed to play an important role. The aim of this study was to test the effects of heat stress on HRR and HR variability (HRV) after aerobic exercise in healthy subjects. Twelve healthy males (25±1 yrs, 23.8±0.5 kg/m2) performed 14 min of moderate-intensity cycling exercise (40 - 60% HRreserve) followed by 5 min of loadless active recovery in two conditions: heat stress (HS) and normothermia (NT). In HS, subjects dressed in a whole-body water-perfused tube-lined suit to increase internal temperature (Tc) by ~1°C. In NT, subjects did not wear the suit. HR, core and skin temperatures (Tc and Tsk), mean arterial pressure (MAP) skin blood flow (SKBF) and cutaneous vascular conductance (CVC) were measured throughout and analyzed during post-exercise recovery. HRR was assessed through calculations of HR decay after 60 and 300 s of recovery (HRR60s and HRR300s), and the short- and long-term time constants of HRR (T30 and HRRt). Post-exercise HRV was examined via calculations of RMSSD (root mean square of successive RR intervals) and RMS (root mean square residual of RR intervals). The HS protocol promoted significant thermal stress and hemodynamic adjustments during the recovery (HS-NT differences: Tc = +0.7±0.3 ºC; Tsk = +3.2±1.5 ºC; MAP = -12±14 mmHg; SKBF = +90±80 a.u; CVC = +1.5±1.3 a.u./mmHg). HRR and post-exercise HRV were significantly delayed in HS (e.g. HRR60s = 27±9 vs. 44 ± 12 bpm, P<0.01; HRR300s = 39±12 vs. 59±16 bpm, P<0.01). The effects of heat stress (e.g., the HS-NT differences) on HRR were associated with its effects on thermal and hemodynamic responses. In conclusion, heat stress delays HRR, and this effect seems to be mediated by an attenuated parasympathetic reactivation and sympathetic withdrawal after exercise. In addition, the impact of heat stress on HRR is related to the magnitude of the heat stress-induced thermal stress and hemodynamic changes.